2015
DOI: 10.1186/s40169-015-0051-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of fatigue related to adjuvant chemotherapy for breast cancer: evaluation of plasma and lymphocyte expression

Abstract: Background Fatigue is common in cancer patients receiving adjuvant chemotherapy. To further understand the mechanism of fatigue and search for potential biomarkers, we conducted this prospective study. Methods We enrolled breast cancer (BC) patients before their first adjuvant Adriamycin-based chemotherapy cycle. Patients responded to the brief fatigue inventory (BFI) and Chalder fatigue questionnaires and had their blood drawn for both plasma evaluation and evaluation of the peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…Mental arithmetic and public speech stressors also performedLennartsson [24]201556H/BDCSRD; exclusion w/ SEQDHEA-S; ACTH; ACTH and DHEA-S post-TSST (TSST stress test performed)↓DHEA-S, ↓post-TSST DHEA-S, Nl ACTH, Nl post-TSST ACTHTao [23]2015171H/BMaslachMSC, ACTH↑ACTH, ↑MSCJonsson [29]201551H/BSMBQMSC, MSTNl MSC, ↓MSTLennartsson [27]201556H/BDCSRD and SMBQMSC, MST, ACTH, ACTH post-TSST (TSST stress test performed)Nl MSC, Nl MST, Nl ACTH, Nl post-TSST ACTHSevere BO: lower ACTH, cortisol response to TSST vs controls, whereas low BO: higher ACTH, cortisol responses vs controlsSchmaling [26]201562HealthyADASAUC, SCR↓AUC, ↓SCR31 couples studied, one of which had chronic fatigue (but not CFS)Sveinsdottir [68]20151150Chronic LombalgiaCFQDAC, CAR, SCR, NSCNl DAC, Nl CAR, Nl NSC, Nl SCR**Colocar como SAUDÁVEL – porque é só lombalgia (increased CAR in Low back pain)Powell [67]201576Multiple SclerosisCFQDAC, CAR, SCR↓DAC, ↑CAR, Nl SCRSleep disorders excluded; adjusted for depressive symptoms; NSC not published. Multiple sclerosis had increased awakening cortisol and decreased CARCruz [70]201543Breast cancerBFI and CFQMSC, DHEA-SNl MSC, Nl DHEA-SPts undergoing ChTx included anthracyclinesMarchand [31]20141043H/BMaslachDAC, CAR, SCR, NSC↑DAC, ↓CAR, ↑SCR, ↓NSCOnly BO; Groups of severe distress or depression not includedAggarwal [30]2014227HealthyCFQMSC, NSC, 0.25 mg DST, DHEA-SNl MSC, Nl NSC, Nl 0.25 mg DST, ↓DHEA-SEvaluation of chronic, widespread pain, chronic orofacial pain, chronic fatigue (but not CFS), irritable bowel syndromeTell D [71]2014130Breast cancerMFIDAC, CAR, SCR,...…”
Section: Resultsmentioning
confidence: 99%
“…Mental arithmetic and public speech stressors also performedLennartsson [24]201556H/BDCSRD; exclusion w/ SEQDHEA-S; ACTH; ACTH and DHEA-S post-TSST (TSST stress test performed)↓DHEA-S, ↓post-TSST DHEA-S, Nl ACTH, Nl post-TSST ACTHTao [23]2015171H/BMaslachMSC, ACTH↑ACTH, ↑MSCJonsson [29]201551H/BSMBQMSC, MSTNl MSC, ↓MSTLennartsson [27]201556H/BDCSRD and SMBQMSC, MST, ACTH, ACTH post-TSST (TSST stress test performed)Nl MSC, Nl MST, Nl ACTH, Nl post-TSST ACTHSevere BO: lower ACTH, cortisol response to TSST vs controls, whereas low BO: higher ACTH, cortisol responses vs controlsSchmaling [26]201562HealthyADASAUC, SCR↓AUC, ↓SCR31 couples studied, one of which had chronic fatigue (but not CFS)Sveinsdottir [68]20151150Chronic LombalgiaCFQDAC, CAR, SCR, NSCNl DAC, Nl CAR, Nl NSC, Nl SCR**Colocar como SAUDÁVEL – porque é só lombalgia (increased CAR in Low back pain)Powell [67]201576Multiple SclerosisCFQDAC, CAR, SCR↓DAC, ↑CAR, Nl SCRSleep disorders excluded; adjusted for depressive symptoms; NSC not published. Multiple sclerosis had increased awakening cortisol and decreased CARCruz [70]201543Breast cancerBFI and CFQMSC, DHEA-SNl MSC, Nl DHEA-SPts undergoing ChTx included anthracyclinesMarchand [31]20141043H/BMaslachDAC, CAR, SCR, NSC↑DAC, ↓CAR, ↑SCR, ↓NSCOnly BO; Groups of severe distress or depression not includedAggarwal [30]2014227HealthyCFQMSC, NSC, 0.25 mg DST, DHEA-SNl MSC, Nl NSC, Nl 0.25 mg DST, ↓DHEA-SEvaluation of chronic, widespread pain, chronic orofacial pain, chronic fatigue (but not CFS), irritable bowel syndromeTell D [71]2014130Breast cancerMFIDAC, CAR, SCR,...…”
Section: Resultsmentioning
confidence: 99%
“…of the FRD intervention may have facilitated decreased fatigue and improved sleep quality. A likely mechanism through which the FRD is working is by decreasing chronic inflammation and modulating immune activation [11, 46], and in particular, decreasing circulating inflammatory biomarkers CRP, Interleukin-6 (IL-6), and interleukin 1 receptor antagonist (IL-1RA), which are associated with fatigue in cancer patients [21, 43, 47, 56]. We have previously reported that individuals who eat diets high in antioxidant micronutrients [19], or have high intake of whole foods including fish, fruits, and vegetables, similar to the FRD, have significantly lower concentrations of circulating inflammatory biomarkers [4, 14, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Immunoassays selective for osteoclastic TRACP5b are now well established and clinically relevant. 33 In the past, many studies had specifically shown the association between symptom distress and inflammatory biomarker in cancer patients such as breast cancer, 34,35 colorectal or esophageal cancer, 36 and ovarian cancer. 37 Of them, no study discusses about the role of TRACP5a in lung cancer patients.…”
mentioning
confidence: 99%